CJ 4/241: Allegations of brutality against RUC and Army : (Adam Matthew Digital, 2013)
Description: Cases submitted by Fr D Faul, Fr R Murray and others. Detailed statements. Statement in House of Commons; correspondence with MOD and 10 Downing Street.